Educación sexual en adolescentes de 12 a 16 años del Colegio Eugenio Espejo, Babahoyo, Los Ríos, octubre 2018 ¬¬¬-abril 2019 - Coello Gavilanez, Juan Javier (2019)
Sex education is a term used to define education about sex, refers in itself to sexuality, what is the reproductive system (female and male), sexual orientation, sexual relations, the use of contraceptive methods, sex safe and more specifically human reproduction. Whose main objective is to determine how sex education influences and its relation in pregnancies of adolescents from 12 to 16 years of age Eugenio Espejo Babahoyo School October 2018 April 2019. This study is quantitative cross-sectional descriptive type, since it will recognize the sites that they will allow access to research. In this work, the sample consisted of 120 students, prior to the signature of the informed consent, a direct survey was conducted to obtain and tabulate the data. It was evidenced that 92% are students from 12 to 14 years old, while 8% are from 15 to 16, they were asked if in their school they have received training on sexual education, which 8% answered yes, while 92% did not, about the pathologies that occur through copulation 30% if you know while 70% do not know, about the risks that occur in pregnancy during adolescence 42% if you know while 58% do not know. In conclusion it was possible to demonstrate that the lack of orientation makes young people can make wrong decisions, it is important that they always stay informed because pregnancies at this age are very risky.